LEGAL PERSPECTIVES OF KUA HEADS ON ISSUING FAMILY CARDS FOR UNREGISTERED MARRIAGES IN TANJUNGPINANG - Yunus, Hanafi; Andini, Lintang Tri; Hidayat, Taufik (FOCUS: Jurnal of Law, 2025)
This study examines the legal perspectives of KUA heads in Tanjungpinang regarding the issuance of Family Cards for unregistered marriages under Permendagri No. 109 of 2019. It analyzes the tension between Islamic law and state administrative requirements, focusing on ethical dilemmas and administrative challenges faced by KUA officials. A qualitative descriptive approach was employed, using semi-structured interviews with KUA heads and document analysis of relevant regulations. Findings suggest that KUA officials recognize unregistered marriages as valid under Islamic law but not legally acknowledged by the state, leading to careful administrative practices. The study highlights the need for policy harmonization to ensure consistency and protect citizens' rights.